2022
DOI: 10.3390/f13081315
|View full text |Cite
|
Sign up to set email alerts
|

The Climate-Growth Relationship between Picea smithiana (Wall.) Boiss. and Abies pindrow (Royle ex D.Don) Royle along the Latitudinal Gradient in Northern Pakistan

Abstract: A changing climate and global warming have adversely affected Pakistan’s moist and dry temperate vegetation. Abies pindrow (fir) (Royle ex D.Don) Royle and Picea smithiana (spruce) Wall.) Boiss are the two major representative species of the moist and dry temperate forests in Northern Pakistan. The dendroclimatic study of both species is crucial for the assessment of climate variability at various spatial and temporal scales. This study examined the dendroclimatology of fir and spruce, and analyzed the growth–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 103 publications
2
1
0
Order By: Relevance
“…Therefore, response of tree-growth to temperature is not uniform across the whole of Pakistan because some trees from high elevation regions are showing positive responses to temperature, while those from dry sites are showing negative responses to temperature. Similar to the present study, a negative response of Picea smithiana with the spring season temperature has been reported in the Karakoram region of northern Pakistan 60 , with the same for the C. deodara from the Hindu Kush range of Pakistan 61 . Similarly, Zafar et al 62 found a negative relationship between temperatures and the P. smithiana and P. gerardiana chronologies from the Gilgit and Hunza valleys of northern Karakorum during most of the months of recent years.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, response of tree-growth to temperature is not uniform across the whole of Pakistan because some trees from high elevation regions are showing positive responses to temperature, while those from dry sites are showing negative responses to temperature. Similar to the present study, a negative response of Picea smithiana with the spring season temperature has been reported in the Karakoram region of northern Pakistan 60 , with the same for the C. deodara from the Hindu Kush range of Pakistan 61 . Similarly, Zafar et al 62 found a negative relationship between temperatures and the P. smithiana and P. gerardiana chronologies from the Gilgit and Hunza valleys of northern Karakorum during most of the months of recent years.…”
Section: Discussionsupporting
confidence: 91%
“…The climate growth response of both species against climatic parameters was similar. The growth of both species was positively correlated with precipitation and negatively correlated with temperature, similar to the findings of Ullah et al (2022) and Ahmed et al (2010). In dry temperate regions, precipitation becomes the limiting factor for growth of conifer species, and lack of rainfall with increasing temperature results in drought conditions, leading to decreased growth rate of trees (Thapa et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Pindrow and T. baccata are more vulnerable to climate changes (Thapa et al 2013, Yousaf et al 2022. These two species in this temperate forest are dominant (Muhammad et al 2021), having rapid growth and according to recent studies these species have potential sensitivity for dendroclimatological studies (Thapa et al 2013, Shaheen et al 2015, Koc et al 2018, Ullah et al 2022. However, little is known on the relationship between climate and growth for these two species in the study site, we explored this correlation with regional temperature and precipitation variability to assess their potential for climate reconstruction.…”
Section: Introductionmentioning
confidence: 98%